2019
DOI: 10.1186/s12888-019-2379-x
|View full text |Cite
|
Sign up to set email alerts
|

European violence risk and mental disorders (EU-VIORMED): a multi-centre prospective cohort study protocol

Abstract: BackgroundThe link between schizophrenia spectrum disorders (SSD) and violence is a core issue for most forensic psychiatric services. However, the drivers of violence in this population remain unclear, and, to date tools to predict violence risk have a range of limitations. Perhaps because of this uncertainty about the nature of violence risk, treatment programmes and care pathways for mentally disordered offenders vary substantially across the European Union, and differences in legal and policy frameworks ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 85 publications
0
11
0
1
Order By: Relevance
“…EU-VIORMED is a European multicentre observational study [ 21 ]. The field work was conducted in five European countries: Austria, Germany, Italy, Poland and the United Kingdom.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…EU-VIORMED is a European multicentre observational study [ 21 ]. The field work was conducted in five European countries: Austria, Germany, Italy, Poland and the United Kingdom.…”
Section: Methodsmentioning
confidence: 99%
“…The power analysis and the computation of the sample size had been exhaustively described in the study protocol [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…According to several studies [62][63][64][65], having a mental disease with severe symptoms is associated with a higher probability of any form of aggressive behavior. Recent investigations identify schizophrenia, cognitive impairment, anxiety, acute stress reaction, suicidal ideation, along with poor insight, personality disorders, impulsivity, and psychopathy as the clinical factors with the strongest empirical evidence for association with violence [66,67].…”
Section: Psychiatric Diagnosismentioning
confidence: 99%
“…The evaluation process includes many tools and will take some time to be completed, especially for the participants who will be enrolled in all three studies. Although this may lead to high refusal rates, previous experience with health services research carried out in Italy has shown that, due to the high degree of collaboration between staff and patients, refusal rates can be kept very low [43,44,89,90].…”
Section: Limitationsmentioning
confidence: 99%